Relation between cybernetics and information security: from Norbert Wiener's perspectives. Issue 10 (6th November 2017) - Anjaria, Kushal; Mishra, Arun
Abstract : Purpose: Nowadays, to design the information security mechanism for computing and communication systems, there are various approaches available like cryptographic approach, game-theoretic approach, quantitative–qualitative analysis-based approach, cognitive-behavioral approach, digital forensic-based approach and swarm computing-based approach. The contemporary research in these various fields is independent in nature. The purpose of this paper is to investigate the relationship between these various approaches to information security and cybernetics. Design/methodology/approach: To investigate the relationship between information security mechanisms and cybernetics, Norbert Wiener's concepts and philosophy of the cybernetics have been used in the present work. For a detailed study, concepts, techniques and philosophy of the cybernetics have been extracted from the books of Norbert Wiener titled "The human use of human beings" and "Cybernetics or control and communication in the animal and the machine". Findings: By revisiting the concepts of the cybernetics from the information security perspectives, it has been found that the aspects of information security and the aspects of cybernetics have great bonding. Originality/value: The present paper demonstrates how bonding between cybernetics and information security can be used to solve some of the complex research challenges in information security area.